A vocal health survey among primary school teachers in Klang Valley, Malaysia - How, Dim Sy; Ang, Mei Foong (Human Resource Management Academic Research Society, 2021)
Teachers are one of the highest demanding professional voice users. They are believed to have an increased risk of developing voice disorder, and the cause is often associated with several factors such as high vocal demands, unfavourable working conditions, lifestyle, and lack of knowledge in vocal health. Vocal disorder not only affects teachers in conducting and managing classes. It also affects their daily interaction with people and contributes to the decline of their physical and emotional health. This study aims to understand teachers' current vocal condition better and measure teachers' knowledge of vocal care. An online survey was conducted; 40 teachers, 33 females and 7 males, responded to the study. The study reviewed that teachers voice feels dry (51.22%), sore (24.39%) and pain (12.20%) after a day of teaching and 78% of the teachers experience at least once vocal discomfort in a year. In conclusion, the insights and perception of vocal health base on self-report information of voice condition and lifestyle of teachers pertinent to this geographical location will be helpful in the development of vocal health programs for teachers in Malaysia.